Gastrointestinal Ulceration as a Manifestation of Severe Dermatomyositis -: A Case Report - O’Shea, Daniel (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.